The influence of fitness mobile apps on workout behavior intention among Chinese young adults - Mengyu Li; Shujie Wang; Abdul Rahim Ahmed Soliman Darweesh (PLoS ONE, 2025)
Exercise was one of the most widely promoted methods to improve physical health while socially restricted. Despite the extensive notion of the advantages of sports activities, many young adults in China do not get the suggested amount of physical activity. Moreover, little is known about how one’s intentions regarding workout behavior are connected to one’s beliefs about using fitness mobile apps. The present study put into effect an online survey with random respondents of 5686 adults to examine a model combining the theory of planned behavior and the health belief model to predict Chinese adults’ attitudes, subjective norms, and perceived behavioral control when using fitness apps to work out, and to investigate associations between users’ beliefs and workout behavior intentions. The three main independent variables assessed were (1) attitude, (2) subjective norms, and (3) perceived behavioral control. Three components of belief were examined: self-efficiency, perceived barriers, and perceived benefits. The analyses found that attitudes and perceived behavioral control were positive and significant correlates of workout behavior intentions. The analysis also found that subjective norms were insignificantly associated with workout behavior intentions. Finally, the moderation test showed that belief moderated the assignations between the independent factors and workout behavior intentions. The findings suggest that the role of predictors within an integrated model using planned behavior theory and the health beliefs models provides a valid framework in the Chinese context of fitness app users. The research results have implications for the advancement and improvement of mobile phone apps that provide fitness functions, as well as for encouraging Chinese adults to promote the quantity and quality of their sport exercise.